VALENCY DICTIONARIES AND TURKISH - Nuh DOĞAN (Fırat University, 2019)
In the dictionaries of European languages, what arguments verbs and other lexical items take and what meanings these collocations create are listed in detail. In Turkish dictionaries, however, the case-marked arguments verbs can take are either given incompletely, disorderly, wrongly, or not given at all. Valency dictionaries serve as a source of reference for describing the morphological information of lexical items while preparing general purpose dictionaries. Valency dictionary is a type of dictionary that lists in a detailed fashion the logical, syntactic, morphological, semantic and collocational conditions and limits of lexical items and various structures that are formed accordingly. In world languages, valency of lexical items and valency dictionaries that consists of this information have attracted extensive attention, and such dictionaries for many languages, European languages in particular, have been published. It is seen that valency dictionaries, giving detailed information on the logical, syntactic and semantic structures of natural languages, have drawn little attention and been neglected in Turkish. Valency dictionaries contribute to different fields in various ways. Besides de-fining a language in terms of logical, syntactic and semantic aspects, valency dictionaries provides researchers with invaluable information regarding language teaching, natural language processing and dictionary production. The structure of a valency dictionary consists of different components. In general, various types of information can be clarified in a valency dictionary such as the number of arguments a lexical item requires for a specific meaning, the type and function of arguments, their syntactic valency structure, the morphological limitations of arguments, obligatory, optional and contextual arguments, syntactically strict positions, collocational limitations, alternative arguments and structures, variations of valency according to voice, semantic roles arguments take, optional limitations arguments carry and semantic valency structures. Valency dictionaries can change in line with the priorities and needs of the dictionary makers.